Racinality of NSAID Use on Osteoathritis Patients in the Army Hospital of Pematang Siantar - Ismi Noer Faridah (PT Inovasi Pratama Internasional, 2022)
Rational Use Of Medicine (RUM) or known as Rational Use of Medicine (POR) is a campaign that is spread throughout the world, also in Indonesia. The formulation of the problem in this study is how the rationality of the use of NSAIDs in osteoarthritis patients who seek treatment at the Pematangsiantar Army Hospital. This research was carried out on outpatients at the Pematangsiantar City Army Hospital for the April-June 2021 period . Research data collection was carried out in July-August 2021. Rationality in terms of 5 accuracy (right diagnosis, right indication, right drug, right dose and right patient) then we get the results of the analysis that some of the accuracy is 100% correct, while for the right drug parameter it is still worth 52%. So it can be concluded that treatment for Osteoarthritis patients when viewed from the right diagnosis, right indication, right dose, right patient, right drug, right method of administration at the Pematangsiantar City Army Hospital still cannot be fully said to be rational.